2011
DOI: 10.1038/ajg.2010.342
|View full text |Cite
|
Sign up to set email alerts
|

Potential Precipitating Factors of Esophageal Variceal Bleeding: A Case–Control Study

Abstract: Valsalva maneuver-associated activities such as straining during defecation, vomiting, and cough are believed to cause abrupt increase in variceal pressure. Whether these actions can precipitate rupture of esophageal varices (EV) is unknown. The association of EV bleeding with these activities and other potential risk factors such as ingestion of alcohol and non-steroidal anti-infl ammatory drugs was investigated. METHODS:Between January 2003 and May 2009, 240 patients with liver cirrhosis and acute EV bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Although ALD was associated with poorer prognosis at univariate analysis, we found no difference in cumulative incidence or risk of death without LT according to etiology when controlling for other factors. Interestingly, however, among patients with no previous history of variceal bleeding, alcohol consumption was a strong predictor of first bleeding episode, confirming results from a Taiwanese study [20].…”
Section: Discussionsupporting
confidence: 81%
“…Although ALD was associated with poorer prognosis at univariate analysis, we found no difference in cumulative incidence or risk of death without LT according to etiology when controlling for other factors. Interestingly, however, among patients with no previous history of variceal bleeding, alcohol consumption was a strong predictor of first bleeding episode, confirming results from a Taiwanese study [20].…”
Section: Discussionsupporting
confidence: 81%
“…The risk of esophagogastric variceal bleeding associates with the pressure gradient of hepatic vein, varicose veins grading, red sign and esophagogastric varicose veins [1,2], and the constipation, vomiting, severe cough and alcoholism are the triggers of bleeding [3], while the studies focusing on the influence of season and meteorological factors on the esophagogastric variceal bleeding are less and the results are not unanimous. Tahri and his colleague [4] found that the morbidity of esophagogastric variceal bleeding reached to maximum in winter, OR = 3.2 (95% CI: 1.6 -6.5).…”
Section: Dicussionmentioning
confidence: 99%
“…However, patients are often unwilling to undergo an endoscopic examination without proper sedation. Also, retching or vomiting during nonsedated endoscopic procedures may be associated with an increased risk of incidental variceal bleeding in these patients [4]. Although sedative endoscopy is now a common practice, the safety of the procedure in patients with liver cirrhosis is currently under debate [5].…”
Section: Introductionmentioning
confidence: 99%